Assessment policies on a large scale: analysis based on Weber - Prado, Michelle de Souza [UNESP]; Garcia, Daniela Nogueira de Moraes [UNESP] (Edipucrs-editora Univ Pucrs, 2022)
The following paper is linked to a theoretical approach about a pro-minent issue in Brazilian education, which are large-scale assessments. We aim to make notes on the standardized tests in the school context with the help of Max Weber's sociology. We elected two external assessments. Both tests are from the public school system: the first, Prova Brasil, nationwide, which evalua-tes the fifth and ninth years; and the second, developed by the State Education Department of Sao Paulo, affiliated to the first, entitled Assessment of Learning in Process (Avaliacao de Aprendizagem em Processo, AAP in Portuguese), the latter being the target of our discussions since the formation in the professional master's degree. The arguments start from the analysis of the situation in which the student, the assessed subject, is submitted throughout his career in free schooling to the scales of rationalized measures, as we will highlight through the Weberian theory, which does not take into account aspects such as management, training teaching staff, conditions and funds allocated to educational systems, due to excessive concern about the indexes.
Keywords: Assessment of Learning in Process; Prova Brasil; Weber